2021
DOI: 10.1111/jeb.13871
|View full text |Cite
|
Sign up to set email alerts
|

Capturing the rapidly evolving study of adaptation

Abstract: Research on the genomics of adaptation is rapidly changing. In the last few decades, progress in this area has been driven by methodological advances, not only in the way increasingly large amounts of molecular data are generated (e.g. with high-throughput sequencing), but also in the way these data are analysed. This includes a growing appreciation and quantitative treatment of covariation among units ns.com/publo n/10.1111/jeb.13871.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 110 publications
0
2
0
Order By: Relevance
“…A major goal of evolutionary biology is to identify the relative importance of adaptive evolution through genomic signatures of natural selection (Fruciano et al, 2021). The widespread focus on genome scanning techniques (De Villemereuil et al, 2014), which rely primarily on SNPs, is based on their abundance in the genome (González et al, 2009; Hoban et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…A major goal of evolutionary biology is to identify the relative importance of adaptive evolution through genomic signatures of natural selection (Fruciano et al, 2021). The widespread focus on genome scanning techniques (De Villemereuil et al, 2014), which rely primarily on SNPs, is based on their abundance in the genome (González et al, 2009; Hoban et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The CPLs detected in this study were found located in both gene body and upstream–downstream regions close to genes. The distribution of SNPs in distinct genomic regions is important in evolutionary studies and is now often reported in the literature ( e.g ., Fruciano et al ., 2021; She & Jarosz, 2018). Within pigmentation studies, the literature initially emphasized both the relative roles of coding (Protas & Patel, 2008; Uy et al ., 2016) and upstream‐downstream regulatory variation (Larter et al ., 2018; Toomey et al ., 2018)—more rarely their interactions (Vickrey et al ., 2018)—during colour pattern establishment and evolution.…”
Section: Discussionmentioning
confidence: 99%
“…It denotes the strategic actions and instruments used to anticipate disaster risk; reduce existing exposure, hazard, or vulnerability, as well as improve resilience; considering that environmental stability, hazard threat, and socioeconomic vulnerability together determine the way that disasters are formed, establish the spatial extent of disaster impact, and generate the scale of losses (Shi et al 2020); d) Adaptation actions must respond to the problems identified in the corresponding diagnoses: The prioritization of adaptation actions has to be related to the problems identified in the climate agenda and to the analysis of current and future vulnerability, these measures must consider the participation of social actors. Consequently, it is suggested to meet the following characteristics: 1) Feasible; (2) Budgeted; (3) Synergistic; (4) Co-benefits; (5) Aligned; (6) Evaluable; (7) Equity; (8) Credibility; (9) No Regret; and (10) Reversibility. Monitoring and Evaluation (M&E) of climate change adaptation measures is also a very important step.…”
Section: Is Adaptation Enough To Face Climate Change?mentioning
confidence: 99%